(untitled) (World Bulletin of Public Health, 2025)
Pneumocystis jiroveci pneumonia is a common opportunistic infection affecting immunosuppressed patients. High-resolution CT may be indicated for evaluation of immunosuppressed patients with suspected pneumonia and normal chest radiographic findings. The most common high-resolution CT finding of Pneumocystis jiroveci pneumonia is diffuse ground-glass opacity. Computed tomographic features of pneumonia caused by Pneumocystis jiroveci depend on the stage of the process. High-resolution computed tomography should be used